WATER PARTITIONING BETWEEN MANTLE MINERALS FROM PERIDOTITE XENOLITHS - Grant K.; Ingrin J.; Lorand J.P.; Dumas P. (My University, 2007)
The speciation and amount of water dissolved in nominally anhydrous silicates comprising eight different mantle xenoliths has been quantified using synchrotron micro-FTIR spectroscopy. Samples studied are from six geographic localities and represent a cross-section of the major upper mantle lithologies from a variety of tectonic settings. Clinopyroxene contains between 342 and 413 ppm H2O. Orthopyroxene, olivine and garnet contain 169-201, 3-54 and 0 to <3 ppm h2O, respectively. Pyroxenes water contents and the distribution of water between ortho- and clinopyroxene is identical regardless of sample mineralogy (Dwatercpx/opx = 2.1 ± 0.1). The total water contents of each xenolith are remarkably similar (113 ± 14 ppm H2O). High-resolution spectroscopic traverses show that the concentration and speciation of hydrous defects dissolved in each phase are spatially homogeneous within individual crystals and identical in different crystals interspersed throughout the xenolith. These results suggest that the amount of water dissolved in the silicate phases is in partial equilibrium with the transporting melt. Other features indicate that xenoliths have also preserved OH signatures of equilibrium with the mantle source region: Hydroxyl stretching modes in clinopyroxene show that garnet lherzolites re-equilibrated under more reducing conditions than spinel lherzolites. The distribution of water between pyroxenes and olivine differs according to xenolith mineralogy. The distribution of water between clinopyroxene and olivine from garnet peridotites (Dwatercpx/oliv (gnt) = 22.2 ± 24.1) is a factor of four greater than mineral pairs from spinel-bearing xenoliths (Dwatercpx/oliv (sp) = 88.1 ± 47.8). Such an increase in olivine water contents at the spinel to garnet transition is likely a global phenomenon and this discontinuity could lead to a reduction of the upper mantle viscosity by 0.2-0.7 log units and a reduction of its electrical resistivity by a factor of 0.5-0.8 log units. © Springer-Verlag 2007.
Keywords: CONDUCTIVITY; GARNET LHERZOLITES; HYDROGEN; LITHOSPHERIC MANTLE; MANTLE XENOLITHS; PARTITION COEFFICIENTS; VISCOSITY; WATER